2016
DOI: 10.1063/1.4956448
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of arbitrary amplitude dust-ion acoustic waves in the collisional magnetized dusty plasma in the presence of non-thermal electrons

Abstract: Using the Sagdeev pseudo-potential method, the oblique propagation of dust-ion acoustic solitary waves is studied in a magnetized dusty plasma. By considering non-thermal distribution of electrons, the related pseudo-potential is obtained using the Poisson equation. The behavior of the wave is investigated for some ranges of parameters. It is demonstrated that the increase in ion density, lz, β, and also δ1 can lead to the increases in the width and amplitude of the pseudo-potential, while any increase of a2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…[13] Nonlinear electrostatic and electromagnetic waves have been studied in the presence of different collision phenomenon. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] Nonlinear dust magnetosonic waves with inertia-less ions and electrons in the presence of dust-ion and dust-electron collisions have been studied and was shown that the magnetized, collisional dusty medium can be described by the modified Korteweg-de Vries (mKdV) equation. [28] Nonlinear magnetosonic waves in pair ion plasmas in the presence of ion-electron collisions reveal the emergence of the dissipative structures.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Nonlinear electrostatic and electromagnetic waves have been studied in the presence of different collision phenomenon. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] Nonlinear dust magnetosonic waves with inertia-less ions and electrons in the presence of dust-ion and dust-electron collisions have been studied and was shown that the magnetized, collisional dusty medium can be described by the modified Korteweg-de Vries (mKdV) equation. [28] Nonlinear magnetosonic waves in pair ion plasmas in the presence of ion-electron collisions reveal the emergence of the dissipative structures.…”
Section: Introductionmentioning
confidence: 99%